Schistosomicidal and immunomodulatory effects of Momordica charantia in Schistosoma mansoni-infected mice - Amal Mohamed Shaaban; Hany Mohammed Ibrahim; Azza Hassan Mohamed; Amany Ebrahim Nofal (Egyptian Liver Journal)
Abstract Background The current work was designed to evaluate the influence of Momordica charantia fruit (MCF) supplement alone (200 mg MCF/kg) or with praziquantel (250 mg PZQ/kg) in Schistosoma mansoni-infected mice. Parasitological parameters, scanning electron microscopy (SEM) of male adult worm of S. mansoni, histopathological and immunohistochemical alterations of liver and intestine, antioxidant activity, cytokine changes, and flow cytometric analysis of the blood CD4+ and CD8+ cells were detected. Results The phytochemical screening of bitter melon fruit revealed good contents of phenols and flavonoids. Dual treatment of PZQ plus MCF showed elimination of worm burden as the reduction percentage was (100%) compared to treatment with PZQ alone (44.4%). All treatments revealed a tegumental damage of the parasite associated with a significant decrease in liver and intestine ova count, a significant elevation in the percentages of dead ova, and a partial decrease in granuloma diameter. Dual treatment (PZQ + MCF) had the highest significant decrease in mean number of hepatic and intestinal granuloma diameter; the decrease was (60.59 ± 8.0 and 35.77 ± 7.10), respectively in comparison with the infected group (158.57 ± 34.32 and 69.46 ± 13.56). All these alterations were accompanied by a lowering in the level of IFN-γ (365.40 ± 4.55), and a rise in IL-10 level (76.25 ± 2.78), CD4+ and CD8+ cells (51.18 ± 3.31, 49.68 ± 0.54) respectively in MCF-treated group compared to infected mice (400.90 ± 14.67, 66.90 ± 4.31, 41.58 ± 1.37, 34.78 ± 3.79). The antioxidant status showed a significant increase in infected mice treated alone with MCF or combined with PZQ compared to the infected group. Conclusions These outcomes can deduce that dual treatment (PZQ + MCF) has a curative impact on S. mansoni infection and contribute to reducing hepatic and intestinal histopathological effects via modulating host immune response and antioxidant status.